Community Empowerment Through Social-Business Programs in Qurban Activities in North Sumatera - Bin Masruhen, Mohmed Firdaus (Tamkin Jurnal Pemberdayaan Tazkia, 2024)
Community service activities, known as Abdimas, are executed through targeted social campaigns directed at Muslims in Singapore, Indonesia, and Malaysia. These individuals actively engage in the qurban program in North Sumatra, adopting the sacrificial entrustment scheme. The primary objective of this community service initiative is to empower local goat breeders and facilitate the equitable distribution of sacrificial meat within various regions of North Sumatra, encompassing Tebing Tinggi, Medan, and Deli Serdang. The employed methodology for this community service endeavor adheres to participatory action research (PAR), emphasizing active involvement from diverse stakeholders to effectively attain communal development objectives. The outcomes of the social campaign revealed the enthusiastic participation of 700 Qurbani performers, with 70% originating from Singapore and the remaining 30% hailing from Malaysia and Indonesia. The sacrificial ritual involved 700 goats, resulting in the production of approximately 7,500 packs of sacrificial meat. The subsequent distribution of qurban proceeds engaged village heads, hamlet heads, and local communities in the Tebing Tinggi, Medan, and Deli Serdang areas. This article sheds light on the positive contributions of Abdimas activities, emphasizing the empowerment of local goat breeders and the fostering of community solidarity through the support of the qurban program.